Susceptibility testing of Helicobacter pylori: Comparison of E-test and Disk Diffusion for Metronidazole and Mutations in rdxA gene sequences of Helicobacter pylori strains - laleh mahmoudi; Forough sharifzadeh; Sarah Mousavi; Bahman Pourabbas; Ramin Niknam (Shiraz University of Medical Sciences, 2015)
Metronidazole is a main stay of modern multidrug therapies for Helicobacter pylori (H. pylori) infection. Metronidazole resistance reduces the effectiveness of these combinations. Various methods have been used for the determination of the sensitivity of H. pylori to metronidazole with conflicting results. The aims of this study were: 1) to compare the E-Test and disk diffusion methods for determining the susceptibility of H. pylori to metronidazole; and 2) Metronidazole resistance in H. pylori has been found to be associated with mutations in rdxA. The role of this gene in metronidazole resistance in H. pylori was examined in this study. A total of 46 H. pylori strains from 223 consecutive patients were examined. The E-Test was performed according to the manufacturer's guidelines, and the disk diffusion according to standard procedure using 5-μg metronidazole disks. DNA was extracted from all H. pylori isolates by boiling & phenol-chloroform methods and then Polymerase Chain Reaction (PCR) was performed.  Metronidazole resistance as determined by E-test and disk diffusion methods was 64.3% and 47.6% respectively. None of the resistant or sensitive samples possessed rdxA gene deletion. Disk diffusion method is not reliable in determining metronidazole resistance in H. pylori. An intact rdxA gene has also been reported in metronidazole-resistant H. pylori, suggesting that additional metronidazole resistance mechanisms exist in H. pylori and even molecular methods are not reliable for the detection of resistance.